ONLINE MARKETING ACCESSIBILITY AND BEHAVIOR AMONG BATIK ENTREPRENEURS IN LAWEYAN, SURAKARTA, CENTRAL JAVA - Meutia Sistarani; Indriana Indriana; Rosalin Ayal; Adhi Bawono (EAJ (Economic and Accounting Journal), 2020)
In this study, researchers are evaluating the accessibility of online marketing, the most preferable online shops among consumers and the income earned each month generated through it. This research is using a qualitative method on respondents from the batik entrepreneurs’ in Laweyan, Surakarta, Central Java. The primary and secondary data are collected at every research stage. Those data are further analysed using interactive model data analysis. As a result, it was concluded that batik entrepreneurs in Laweyan are actively engaged with social media, but only a few of them are capable to utilize it for their marketing activities. The main reason is due to the limited human resource capable to run an online shop effectively, therefore most of them prefer to sell their goods in a traditional offline store basis. It is very unfortunate, because we also discovered that among batik entrepreneurs who already applied online marketing, their income has increased significantly. From this research, we suggest batik entrepreneurs in Laweyan, Surakarta, Central Java to actively use online shop as an option to market and distribute their product. They could spare some time, at least once a week, to update their business social media, e-commerce page, or business website. By doing this, batik entrepreneurs could increase their income and wider their business.